2017
DOI: 10.1186/s40035-017-0086-4
|View full text |Cite
|
Sign up to set email alerts
|

Rest tremor revisited: Parkinson’s disease and other disorders

Abstract: Tremor is the most common movement disorder characterized by a rhythmical, involuntary oscillatory movement of a body part. Since distinct diseases can cause similar tremor manifestations and vice-versa, it is challenging to make an accurate diagnosis. This applies particularly for tremor at rest. This entity was only rarely studied in the past, although a multitude of clinical studies on prevalence and clinical features of tremor in Parkinson’s disease (PD), essential tremor and dystonia, have been carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 69 publications
1
29
0
Order By: Relevance
“…Although different types of tremor may occur in PD patients (Deuschl, Bain, & Brin, 1998), the most common of these is rest tremor. This is a slow, biplanar, pill-rolling, 4-6 Hz tremor in the fully supported limb; the tremor decreases during movement (Chen, Hopfner, Becktepe, & Deuschl, 2017). Despite the high prevalence of tremor among PD patients, it remains one of the most enigmatic hallmarks of this disease, which is an essentially a hypokinetic movement disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Although different types of tremor may occur in PD patients (Deuschl, Bain, & Brin, 1998), the most common of these is rest tremor. This is a slow, biplanar, pill-rolling, 4-6 Hz tremor in the fully supported limb; the tremor decreases during movement (Chen, Hopfner, Becktepe, & Deuschl, 2017). Despite the high prevalence of tremor among PD patients, it remains one of the most enigmatic hallmarks of this disease, which is an essentially a hypokinetic movement disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosing a tremor disorder accurately is challenging as similar clinical entities can be caused by different diseases . Therefore, in the absence of biomarkers, misdiagnoses between tremor in Parkinson's disease (PD), tremor in dystonia (TiD), and essential tremor (ET) frequently occur . Ioflupane‐based single photon emission computed tomography ( 123 I‐FP‐CIT DAT‐SPECT) can assist in differentiating PD from ET and TiD by detecting a presynaptic dopaminergic deficit .…”
mentioning
confidence: 99%
“…1 Therefore, in the absence of biomarkers, misdiagnoses between tremor in Parkinson's disease (PD), tremor in dystonia (TiD), and essential tremor (ET) frequently occur. 2 Ioflupane-based single photon emission computed tomography ( 123 I-FP-CIT DAT-SPECT) can assist in differentiating PD from ET and TiD by detecting a presynaptic dopaminergic deficit. 3 In recent years, quantitative magnet resonance imaging (MRI) markers have been studied as widely available, noninvasive, radiation-free alternative.…”
mentioning
confidence: 99%
“…The current data show that the presence of tremor is not significantly associated with the level of certainty for PD. A possible explanation for this finding could be the presence of tremor associated with dystonia, drug‐induced tremor, or essential tremor (ET) in the elderly . Some patients enrolled in PD studies, with PD, have been found to have normal presynaptic dopaminergic imaging (DaT scan).…”
Section: Discussionmentioning
confidence: 99%